LIVE Baccarat calculations: Macau machine gambling and the production of the post-socialist subject - Simpson, Tim (Journal of cultural economy, 2019)
Following Portugal's return of Macau to the People's Republic of China in 1999, and the subsequent liberalization of the city's 150-year-old casino monopoly, Macau was transformed into the world's most lucrative site of casino gaming. Today Macau attracts more than 30 million annual tourists, the majority of whom are from mainland China. This article analyzes an electronic casino game called LIVE Baccarat, which was created by a Hong Kong biopharmaceutical company, and designed to appeal to Chinese gamblers in Macau. Drawing on the work of Michel Callon and Michel Foucault, I explore the ways in which the LIVE Baccarat gaming machine 'economizes' the game of baccarat by introducing novel betting functions which require gamblers to engage in various forms of financial calculation, including calqulation, hedging, arbitrage, and portfolio management. LIVE Baccarat is a biopolitical apparatus of subjection of a post-socialist Chinese homo economicus, a form of 'human capital' which Foucault might call an 'entrepreneur of the self.' This subject not only plays a remunerative role in Macau's gaming industry, but conforms to China's macroeconomic goals to engender 'quality' citizens equipped to support a domestic consumer market which may supplant the unsustainable production-for-export regime that drove the country's initial post-reform development.